2022
DOI: 10.1038/s41598-022-14927-y
|View full text |Cite
|
Sign up to set email alerts
|

Psoas muscle index and psoas muscle density as predictors of mortality in patients undergoing hemodialysis

Abstract: This study aimed to investigate the associations of computed tomography (CT)-measured psoas muscle index (PMI: psoas muscle area normalized by height) and psoas muscle density (PMD: average of bilateral psoas muscle CT values [Hounsfield unit (HU)]) with mortality in patients undergoing hemodialysis. We included 188 hemodialysis patients who underwent abdominal CT. PMI and PMD were measured at the third lumbar vertebral level. We found that PMI and PMD were independently associated with the geriatric nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Skeletal muscle mass and quality can be assessed by cross‐sectional skeletal muscle area and skeletal muscle density 11 . Yajima et al found that CT‐measured lower psoas muscle index and lower psoas muscle density at L3 were independently associated with an increased risk of all‐cause mortality in patients undergoing HD (>6 months) 32 . Recently, some studies found that muscle density instead of muscle mass may represent a more clinically meaningful surrogate of muscle function 13,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle mass and quality can be assessed by cross‐sectional skeletal muscle area and skeletal muscle density 11 . Yajima et al found that CT‐measured lower psoas muscle index and lower psoas muscle density at L3 were independently associated with an increased risk of all‐cause mortality in patients undergoing HD (>6 months) 32 . Recently, some studies found that muscle density instead of muscle mass may represent a more clinically meaningful surrogate of muscle function 13,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Using CT muscle density as a surrogate of muscle quality is advantageous for several reasons: it is objective, independent of patient volition, and accessible to all patients who receive a CT scan, regardless of their cognitive, mobility, or conscious status. Muscle density is also predictive of survival in many clinical populations, including heart failure, 21,22 cancer, 3,23,24 COVID-19, 25 and many others 2,26–30 . Before CT muscle density can be effectively utilized as a method of diagnosing muscle wasting diseases and predicting survival, cut points for healthy muscle density must be established and be applicable to contrast and NC exams.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle density is also predictive of survival in many clinical populations, including heart failure, 21,22 cancer, 3,23,24 COVID-19, 25 and many others. 2,[26][27][28][29][30] Before CT muscle density can be Each correction was applied to arterial data (middle column), venous data, (right column), or both. Differences between corrected contrast scan densities and non-contrast scan densities are shown in HU with 95% CIs in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…A common element of PEW and sarcopenia is muscle wasting or loss of muscle; therefore, hemodialysis patients can concomitantly have PEW and sarcopenia [3,4]. We recently reported that computed tomography-measured sarcopenic indices are promising indicators of mortality in hemodialysis patients [12][13][14][15]. According to the Asian Working Group for Sarcopenia: 2019 Consensus Update on Sarcopenia Diagnosis and Treatment, muscle function, such as muscle strength, is considered more important than muscle mass for predicting sarcopenia and mortality in the general population [10].…”
Section: Introductionmentioning
confidence: 99%